Ethanol sensing properties and dominant sensing mechanism of NiO-decorated SnO2 nanorod sensors - Sun, Gun-Joo; Lee, Jae Kyung; Lee, Wan In; Dwivedi, Ram Prakash; Lee, Chongmu; Ko, Taegyung (Electronic materials letters, 2017)
NiO-decorated SnO 2 nanorods were synthesized by the thermal evaporation of Sn powders followed by the solvothermal deposition of NiO. A multi-networked p - n heterostructured nanorod sensor was fabricated by dropping the p -NiO-decorated n -SnO 2 nanorods onto the interdigited electrode pattern and then annealing. The multi-networked p - n heterostructured nanorod sensor exhibited enhanced response to ethanol compared with the pristine SnO 2 nanorod and NiO nanoparticle sensors. The former also exhibited a shorter sensing time for ethanol. Both sensors exhibited selectivity for ethanol over other volatile organic compounds (VOCs) such as HCHO, methanol, benzene and toluene and the decorated sensor exhibited superior selectivity to the other two sensors. In addition, the dominant sensing mechanism is discussed in detail by comparing the sensing properties and current-voltage characteristics of a p -NiO/ n -SnO 2 heterostructured nanorod sensor with those of a pristine SnO 2 nanorod sensor and a pristine NiO nanoparticle sensor. Of the two competing electronic mechanisms: a potential barrier-controlled carrier transport mechanism at a NiO-SnO 2 p - n junction and a surface-depletio n -controlled carrier transport mechanism, the former has some contribution to the enhanced gas sensing performance of the p - n heterostructured nanorod sensor, however, its contribution is not as significant as that of the latter.